Utilising speechace to enhance speaking skills among English as a Second Language pre-university students - Zainuddin, Nur Mazliyana; Mohamad, Maslawati (Human Resource Management Academic Research Society, 2024)
Speaking skills present a significant challenge for second language learners, and recent technological advancements have brought Artificial Intelligence (AI) applications into the forefront of language learning and teaching. The implementation of Speechace as an AI-based tool represents a potential opportunity to enhance the speaking skills of English as a Second Language (ESL) students; therefore, this study aims to describe and analyse the use of Speechace to improve learners’ speaking skills. Guided by the Technology Acceptance Model (TAM), a mixed-method design was employed where 4-point Likert scale questionnaires were administered among 121 pre-university students, and a semi-structured interview was conducted with two teachers. The quantitative data were analysed using descriptive statistics while the qualitative data were analysed using thematic analysis. The study’s findings indicate that student participants agree that Speechace is useful (M=3.51) and easy to use (M=3.39), and they exhibit a positive attitude(M=3.40) and strong behavioural intentions towards using Speechace (M=3.21). In addition, teachers exhibit positive attitudes towards the implementation of Speechace as one of the pedagogical tools in ESL-speaking classrooms. The findings of this study will contribute to a better exploration of students’ perceptions of the use of AI tools in ESL classrooms and provide valuable insights for ESL educators and researchers which align with innovative pedagogies. Furthermore, these insights support achieving Sustainable Development Goal 4 (SDG 4) by promoting inclusive and equitable quality education and lifelong learning opportunities for all.